The Influence of Proximity to Wild Resources and Markets on the Utilization of Wild Edible Plants in Kondoa District, Tanzania (Tanzania Journal for Population studies and Development, 2021)
Wild edible plants (WEPs) are important not only as a source of nutritional supplements but also as a source of income, serving as safety nets during household shocks in central Tanzania. This article examines the influence of proximity to wild resources and markets on the utilization of WEPs. Quantitative and qualitative methods were used in data collection and analysis. These included household survey, focus group discussions, and interviews. The results revealed that proximity to forest/wild areas influences the collection of WEPs over space and time. Subsistence utilization is influenced by proximity to wild resource areas, culminating in the lack of adequate markets and job opportunities. Cash income from WEPs trade is influenced by climate change, processing, means of transport and membership in social networks. Extension services to smallholder farmers can attribute to the synchronization of indigenous knowledge in modern farming systems for natural resource integrity. There is a need to harmonize the development and sustainability of natural resource management, food security and income portfolios, particularly in rural livelihoods, and promote the utilization of wild resources.